COMPARATIVE ANALYSIS OF LABOR PAIN LEVELS BETWEEN PRIMARY AND MULTIPPARATE PAIN - Dartiwen Dartiwen (Universitas Muhammadiyah Kudus, 2023)
Pain due to uterine contractions during labor is a normal thing, but pain can also cause anxiety and fatigue in the mother which will negatively affect the progress of labor and fetal well-being. The purpose of the study was to determine the relationship between age, education and parity on labor pain levels and to analyze the differences in pain levels between primiparas and multiparas. The research method uses a quantitative analytic approach with a cross sectional design. The number of samples as many as 65 mothers who gave birth during one year were taken using accidental sampling technique. Assessment of labor pain level using the Numerical Rating Scale (NRS). Data were analyzed using chi square and Mann-Whitney test. The results showed that there was no significant relationship between age and the level of labor pain (p = 0.126), there was no relationship between education and the level of labor pain (p = 0.334), and there was a difference in the level of labor pain in the first stage of the active phase between primiparous and primiparous mothers. multipara p value = 0.007 (0.05). Providing complete information by health workers about pain management during pregnancy check-ups in order to increase the mother's confidence in facing the delivery process. Further research is needed in analyzing the factors that influence labor pain.